Nanogenerators for gas sensing applications - Zhen, Ye-Xuan; Wang, Gong; Li, Yun-Fei; Yu, Yu (Frontiers in Chemistry, 2025)
Gas sensors are now widely employed in many industries due to the rapid speed of industrialization and the growth of the Internet of Things. However, the wearability and mobility of traditional gas sensors are limited by their high reliance on external power sources. Nanogenerators (NGs) can compensate for their power source limitations when paired with gas sensors by transforming the environment’s widely dispersed low-frequency energy into electrical energy, allowing for self-powered gas detection. The paper thoroughly examines the advancements made in the field of NG-based self-powered gas sensor research in recent years. A systematic description is given of the two main types of NG-based self-powered gas sensors. Lastly, the evolution of sensor use in a few typical gas sensing applications is highlighted, and the field’s future development trend is anticipated.